Understanding the Terrestrial Carbon Cycle: An Ecohydrological Perspective. (4th March 2014) - Govind, Ajit; Kumari, Jyothi
Abstract : The terrestrial carbon (C) cycle has a great role in influencing the climate with complex interactions that are spatially and temporally variable and scale-related. Hence, it is essential that we fully understand the scale-specific complexities of the terrestrial C-cycle towards (1) strategic design of monitoring and experimental initiatives and (2) also developing conceptualizations for modeling purposes. These complexities arise due to the nonlinear interactions of various components that govern the fluxes of mass and energy across the soil-plant-atmospheric continuum. Considering the critical role played by hydrological processes in governing the biogeochemical and plant physiological processes, a coupled representation of these three components (collectively referred to as ecohydrological approach) is critical to explain the complexity in the terrestrial C-cycling processes. In this regard, we synthesize the research works conducted in this broad area and bring them to a common platform with an ecohydrological spirit. This could aid in the development of novel concepts of nonlinear ecohydrological interactions and thereby help reduce the current uncertainties in the terrestrial C-cycling process. The usefulness of spatially explicit and process-based ecohydrological models that have tight coupling between hydrological, ecophysiological, and biogeochemical processes is also discussed.